Antibacterial Activities of Ranting Patah Tulang (Euphorbia tirucalli) Extract: Short Communication - Sesilia I. Napa; Theo Da Cunha; Yohanes Buang (Journal of Applied Chemical Science, 2013)
There have been studied the antibacterial activities of ranting patah tulang (euphorbia tirucalli) extracts against the growth of salmonella thyposa (gram negative) bacteria. The study was firstly started to isolate the antibacterial components of euphorbia tirucalli that was soluble in methanol. Thereafter, the methanol solvent was evaporated to yield powder and the powder was used to prepare the extract concentrations in each petri dish as of following levels that were 10.0, 15.0, 20.0, 25.0, 50.0, 80.0, and 100.0 %, respectively. The 0.0 % of euphorbia tirucalli extracts and 1.0 % of erythromycin in each petri dish served as the controls. The results showed that the clear zone of petri dish containing the bacteria and each those extracts were 36.7±5.8, 40.0±10.0, 43.3±5.8, 60.0±10.0, 66.7±5.0, 70.0±10.0, and 76.7±5.8 mm, respectively. The clear zone of both those controls containing the bacteria were 63.3±5.8 mm. Those results indicate that higher extract concentration higher the clear zone area of the petri dish. Therefore, the euphorbia tirucalli extract potentially inhibits the growth of the salmonella thyposa (gram negative) bacteria.